Optimization of Shift Learning System: Its Impact on History Subject Students in Grade XI - Eka Saputra; Trần Ngọc Dũng (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this study is to examine the impact of the shift learning system on the learning outcomes, motivation, and understanding of history subject students in Grade XI at State Senior High School 6, Bengkulu City. Methodology: This study used a qualitative method with a descriptive approach. Data were collected through structured and unstructured interviews, observations, and document reviews. Tools included notebooks, audio recorders, and cameras for documentation. The data analysis followed a four-step process: data collection, reduction, presentation, and verification. No specific software was mentioned for data processing. Main Findings: The shift learning system improves teacher-student interactions and creates a more focused learning environment. Students report better comprehension in smaller classes, while teachers find class management easier. However, challenges include increased teacher workload, uneven understanding due to shorter sessions, and difficulty for some students in adapting to independent tasks. Lecture methods remain effective but may cause boredom among students. Novelty/Originality of this study: This study uniquely explores the specific impact of the shift learning system on history education for Grade XI students in Bengkulu City, focusing on teacher-student interactions, learning outcomes, and material comprehension. It provides new insights into adapting teaching methods in resource-limited settings and offers a local perspective that can guide similar educational policies elsewhere.